Feminism in literature a Gale critical companion - Bomarito, Jessica 1975-; Hunter, Jeffrey W. 1966- (Gale critical companion, 2005)
This six-volume set explores the history of women and feminism throughout literature, from classical antiquity to modern times. Topics covered include misogyny and women's social roles in ancient civilizations, 16th-century women's devotional literature, 17th- and 18th-century women's captivity narratives, the women's suffrage movement in 19th-century America, women writers of the "Lost Generation," lesbian literature, and much more.